Taxonomy and nomenclature of Salix baileyi, S. rehderiana, and S. disperma - He, Li (Phytotaxa, 2018)
Researchers have frequently misapplied the name Salix leveilleana C.K. Schneider to S. baileyi C.K. Schneider. After detailed study of the types, relevant specimens and literature, S. leveilleana is synonymized with S. disperma Roxb. ex D. Don. Salix dolia C.K. Schneider and S. rehderiana C.K. Schneider represent the same taxon; in this study, the later one is chosen. Furthermore, the author perfected the descriptions of S. baileyi, and amend its distribution area to include Hunan and Zhejiang, China.